When is it worth being a self‐compatible hermaphrodite? Context‐dependent effects of self‐pollination on female advantage in gynodioecious Silene nutans. Issue 9 (11th April 2015) - Lahiani, Emna; Touzet, Pascal; Billard, Emmanuelle; Dufay, Mathilde
Abstract : This study investigates empirically how self‐pollination interplays with male sterilty, which are two major traits of plant reproductive systems. Such interactions have been considered by several theoretical studies but never fully verified empirically. In particular, we directly show that being self‐compatible provides hermaphrodites with a reproductive assurance. Our study thus allows a better understanding of reproductive strategies in flowering plants. Abstract: In gynodioecious plant species with nuclear‐cytoplasmic sex determination, females and hermaphrodites plants can coexist whenever female have higher seed fitness than hermaphrodites. Although the effect of self fertilization on seed fitness in hermaphrodites has been considered theoretically, this effect is far from intuitive, because it can either increase the relative seed fitness of the females (if it leads hermaphrodites to produce inbred, low quality offspring) or decrease it (if it provides reproductive assurance to hermaphrodites). Hence, empirical investigation is needed to document whether relative seed fitness varies with whether pollen is or is not limiting to seed production. In the current study, we measured fruit set and seed production in both females and hermaphrodites and the selfing rate in hermaphrodites in two experimental patches that differed in sex ratios in the gynodioecious plant Silene nutans . We found an impact of plant gender, patch, and their interaction, with females suffering from stronger pollen limitation when locally frequent. In the most pollen‐limited situation, the selfing rate of hermaphrodites increased and provided hermaphrodites with a type of reproductive assurance that is not available to females. By integrating both the beneficial (reproductive assurance) and costly effects (through inbreeding depression) of self‐pollination, we showed that whether females did or did not exhibit higher seed fitness depended on the degree of pollen limitation on seed production.